1998
DOI: 10.1109/10.704874
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human joint mechanical properties from single trial data

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 13 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Figure 4a depicts actual and fitted mean trajectories for the three target levels of three subjects with damping indexes corresponding to different behavior; INDEX ~ 1 for critical-damping (subject #4-DARK, UPRIGHT, DOWN), INDEX < 1 for under-damping (subject #1-LIGHT, UPRIGHT, UP), and INDEX > 1 for over-damping (subject #6-DARK, INVERTED, UP). Interestingly, when averaging across subjects, note that the under-damped performances detected previously in illuminated environments for manual tracking (Xu and Hollerbach 1998;Engel et al 2000), elbow joint movements to perturbations (Lacquaniti et al 1982), and goal-directed movements (Bennett et al 1992) were also observed in Table 2 Correlations with mean error r values are provided in cases where significant correlations (P < .05) were observed for the comparisons for all subjects for the given body orientation (ORIENT = UPRIGHT or INVERTED), starting arm position (ARM = DOWN or UP), and target distance for LIGHT and DARK visual conditions combined (ns not significant). The number in parentheses indicates the number of individual subjects with corresponding significant same signed correlations across individual trials (or expected signed correlation for ns outcomes).…”
Section: Modeling and Damping Indexmentioning
confidence: 92%
See 1 more Smart Citation
“…Figure 4a depicts actual and fitted mean trajectories for the three target levels of three subjects with damping indexes corresponding to different behavior; INDEX ~ 1 for critical-damping (subject #4-DARK, UPRIGHT, DOWN), INDEX < 1 for under-damping (subject #1-LIGHT, UPRIGHT, UP), and INDEX > 1 for over-damping (subject #6-DARK, INVERTED, UP). Interestingly, when averaging across subjects, note that the under-damped performances detected previously in illuminated environments for manual tracking (Xu and Hollerbach 1998;Engel et al 2000), elbow joint movements to perturbations (Lacquaniti et al 1982), and goal-directed movements (Bennett et al 1992) were also observed in Table 2 Correlations with mean error r values are provided in cases where significant correlations (P < .05) were observed for the comparisons for all subjects for the given body orientation (ORIENT = UPRIGHT or INVERTED), starting arm position (ARM = DOWN or UP), and target distance for LIGHT and DARK visual conditions combined (ns not significant). The number in parentheses indicates the number of individual subjects with corresponding significant same signed correlations across individual trials (or expected signed correlation for ns outcomes).…”
Section: Modeling and Damping Indexmentioning
confidence: 92%
“…The angular change of the fingertip during manual tracking of moving targets with direction changes was modeled as an under-damped response for most directional changes and approached a critically damped response for the largest directional changes of 150° or more (Engel et al 2000). Under-damped responses were also reported for elbow joint movements during manual tracking (Xu and Hollerbach 1998), to perturbations (Lacquaniti et al 1982) and for goal-directed movements (Bennett et al 1992). In each of these cases, subjects reached or exceeded the targeted goal.…”
Section: Movement Modelingmentioning
confidence: 99%
“…These approaches have been used to estimate both mechanical [4, 5] and physiological systems [610]. However, parametric methods require knowledge of the system structure, thus may not be useful for physiological systems where little is known a priori .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in defining impedance characteristics, stiffness and damping coefficients have been mostly assumed to be variable [61, 167] with resulting dependencies upon deformation and rate of deformation [14]. …”
Section: Factors That Affect Mechanical Impedancementioning
confidence: 99%